POLYMERIC BIOMATERIALS FILM BASED ON POLY(VINYL ALCOHOL) AND FISH SCALE COLLAGEN BY REPETITIVE FREEZE-THAW CYCLES FOLLOWED BY GAMMA IRRADIATION - Dian Pribadi Perkasa; Erizal Erizal; Basril Abbas (Indonesian Journal of Chemistry, 2013)
The polymeric biomaterial film based on poly(vinyl alcohol) (PVA) and fish collagen of Lates calcarifer scale were synthesized by three times freeze-thaw cycles followed by gamma irradiation at varied doses of 0, 10, 20, and 30 kGy respectively. Characteristic of PVA/collagen film as effect of constituting polymers and cross linking methods were investigated using Fourier Transform Infrared (FTIR) spectrophotometer, Differential Scanning Calorimetry (DSC), Universal Testing Machine (UTM), and Chroma Mater. Its gel fraction and swelling kinetic were determined by gravimetry. The result showed that IR spectra of controlled and irradiated film demonstrated characteristic vibration bands of both constituting materials. The DSC analysis revealed that gamma irradiation induced interaction between PVA and collagen at molecular level. Improvement of tensile properties by gamma irradiation was observed on tensile strength at 30 kGy with p < 0.05. Gamma irradiation also significantly (p < 0.05) increased yellowness of PVA/collagen film, reduced swelling kinetic, and increased gel fraction of films.